1998
DOI: 10.1063/1.475894
|View full text |Cite
|
Sign up to set email alerts
|

Total differential cross sections for Ar–CH4 from an ab initio potential

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…This potential has been shown to reproduce much of the experimental data that is currently available. In particular, for the total differential scattering cross sections of argon from methane, the results 97 obtained from this potential are in excellent agreement with experiment. Also, the rotationally inelastic integral cross sections 96 are generally in good agreement with the experimental values of Chapman et al 90 In refs 98 and 99 the spectrum for the binary Ar-CH 4 complex was reported and assigned.…”
Section: Rovibrational Spectrum Of Argon−methanesupporting
confidence: 74%
“…This potential has been shown to reproduce much of the experimental data that is currently available. In particular, for the total differential scattering cross sections of argon from methane, the results 97 obtained from this potential are in excellent agreement with experiment. Also, the rotationally inelastic integral cross sections 96 are generally in good agreement with the experimental values of Chapman et al 90 In refs 98 and 99 the spectrum for the binary Ar-CH 4 complex was reported and assigned.…”
Section: Rovibrational Spectrum Of Argon−methanesupporting
confidence: 74%
“…In addition, ab initio and semi-empirical potentials [32][33][34] have been developed for this system. In the most recent paper on the total differential scattering of argon from methane, the results obtained from recent ab initio potential calculations 35 have been shown to be in excellent agreement with experiment. In particular the position of the rainbow feature in the scattering cross section is well reproduced by the potential surface, suggesting that the corresponding well depth of the potential is realistic.…”
Section: Introductionmentioning
confidence: 64%
“…The spectroscopy and dynamics of van der Waals (vdW) rare-gas clusters doped with molecular impurities have been extensively studied during the last three decades. Among these studies, the pioneering theoretical works of Benny Gerber and co-workers contributed remarkably to the progress of the field. As a result of this extensive research, the behavior of these clusters is, at present, well understood in general. There are, however, some aspects that still require further detailed investigation.…”
Section: Introductionmentioning
confidence: 99%